Student Characteristics and Learning Support Design in Open and Distance Higher Education: Evidence from Universitas Terbuka - Yusup Lintang Cahyo Andrian Putro; Rafika Afriyanti; Helni Sadid Parassa; Fadri Ari Sandi; Agus Priyanto (Universitas Pendidikan Ganesha, 2026)
This study examines student characteristics and their implications for designing adaptive learning support in Open and Distance Higher Education at Universitas Terbuka. Using an exploratory sequential mixed-methods approach, qualitative interviews and observations were conducted to identify key student needs, followed by a survey involving 212 respondents to validate emerging patterns. The analysis integrates Self-Determination Theory (autonomy, competence, and relatedness) and principles of quality improvement to interpret student learning experiences within a flexible distance education environment. The findings reveal that 92% of students belong to early digital native groups and 55% are working students, indicating a strong demand for flexible yet structured learning support. While autonomy is relatively high due to flexible learning arrangements, competence develops through lecturer guidance and institutional support, and relatedness remains moderate, highlighting the need for stronger academic interaction and community-building strategies. Students reported the importance of responsive academic communication, clearer digital learning guidance, and more interactive tutorial design. These results suggest that mapping student characteristics can inform pedagogically oriented learning support, including adaptive tutorial strategies, enhanced lecturer–student interaction, and integrated student support systems. The study contributes to the development of evidence-based academic services that strengthen learning engagement and student experience in open and distance education contexts.